Towards an enhanced pipeline health monitoring system : optical fiber bragg grating (FBG) temperature sensor - Leam, Li Ling (2015)
Increasing natural gas consumption in Singapore has led to an ever expanding network of pipelines for delivery and transportation of gas. These pipes transporting highly pressurized flammable gas often run underground and real-time pipeline health monitoring system is highly essential for detection of the location of small cracks prior to devastating ruptures. Over the years, different techniques such as non-optical systems have been developed to measure leakage in gas pipelines. However, most of these methods are very expensive and incapable of detecting the exact leak location. Optical based monitoring techniques like Fiber Bragg grating (FBG) are cheap and safe and can potentially be used for the real-time condition monitoring of gas pipelines. Already, FBGs have been demonstrated for the sensing of temperature and strain, both of which are critical in determining the structural health of pipelines. In this thesis, we investigate the effect of metallization on the temperature sensitivity of FBG. The temperature sensitivity of 1.31 ± 0.09 µm, 6.10 ± 0.9 µm, 8.52 ± 0.6 µm and 13.17±1.15 µm thick nickel coated FBG sensors were 0.01203 nm/°C, 0.01427 nm/°C, 0.01505 nm/°C and 0.01627 nm/°C respectively, representing a significant improvement over uncoated FBG. The thickness of the metal is found to have a direct correlation with temperature sensitivity. The hysteresis of the metal coated fiber is less than 1 % and the limit of detection is less than 0.2°C. Crucially, the FBGs can be connected in series along an optical fiber to carry out simultaneous temperature measurement of multiple locations. Thus, the fabricated FBG temperature sensors can potentially be used as a component of an optical system for early detection of gas leakage in pipelines.